2022
DOI: 10.1007/s00455-022-10437-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes and Patient Safety of Nasogastric Tube in Acute Stroke Patients

Abstract: Nasogastric tube (NGT) is often used in stroke patients who are dysphagic (deglutition disorders) or have decreased conscious state. This method of feeding is assumed to have minimal complications. The aim of this study is to analyze complications associated with NGT and variables associated with mortality. Retrospective analysis of 250 acute stroke patients requiring NGT feeding between 2003 and 2020. There were 250 patients (median age 76 (IQR 68–83), 56.4% males, median time to NGT 1 day (IQR 0–3). Discussi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
13

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 24 publications
0
7
0
13
Order By: Relevance
“…Moreover, we perceived resistance in the middle or lower esophagus, and discontinued the insertion any further in four patients. This was probably due to the esophageal stenosis or hiatus hernia [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we perceived resistance in the middle or lower esophagus, and discontinued the insertion any further in four patients. This was probably due to the esophageal stenosis or hiatus hernia [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that complications associated with NGT insertion, such as wrong placements, pneumothorax, bleeding, and mucosal injury were more prone to occur in patients with obesity [ 18 ] and acute stroke [ 17 ], who experience difficult insertion. In our study, we focused on the laryngopharyngeal mucosal injury due to blind NGT insertion during CPR.…”
Section: Discussionmentioning
confidence: 99%
“…Stroke-associated pneumonia is more prevalent in patients treated in a medical ICU, with twenty-one per cent to fortyfour per cent needing tube feeding (14).Pneumonia is the primary cause of fever in the initial 48 hours following an acute stroke. It is also commonly associated with frequent health complications within 30 days of stroke episode (15) .…”
Section: Discussionmentioning
confidence: 99%
“…NGTs in such patients are most often used for feeding. Another study in acute stroke patients by Rabaut et al [ 46 ] revealed that multiple serious complications could occur with the use of NGT. These included aspiration pneumonia (49.2%), multiple insertion attempts, failed insertions, reinsertions, placement in the wrong positions, resistance, kinking or coiling of NGT, pneumothorax, and death in 36.4% of patients during the hospital admission.…”
Section: Ngt and Nutritionmentioning
confidence: 99%